Willingness To Pay And Ability To Pay Child Follow-Up Immunization In Medan City - Dasopang, Eva Sartika; Julia Sari, Tahara; Muliani, Wina; Hasanah, Fenny; Natalia Siahaan, Desy; Handayani Lubis, Salma (Publisher Cv. Inara, 2024)
Immunization must be given to children starting from infancy and is a mandatory program from the government. Immunization can be provided free of charge at community health centers but can also be paid (carried out independently) at other health service facilities such as private clinics. The aim of this research is to determine the factors that influence Willingness To Pay and Ability To Pay at the Medan South Area Health Center and Rumah Zakat Pratama Clinic in Medan City.This type of research is quantitative research with descriptive analytics using cross sectional methods. Research data was obtained using a questionnaire given to 150 respondents from both research sites, namely the health center and clinic. Job criteria are education and knowledge for willingness to pay, while number of family members, accessibility, income and expenses are associated with ability to pay. Data analysis to see the relationship used the chisquare test (?=0.05).The results of the research show that there is a relationship between education, work and knowledge among respondents at community health centers and clinics with willingness to pay (WTP) with p<0.05 and there is a significant relationship between respondents at both community health centers and clinics where accessibility criteria are met. ability to pay (ATP) with a p value <0.05.